2021
DOI: 10.1016/j.jbc.2021.100668
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of metabolic pathways of 25-hydroxyvitamin D3 mediated by CYP24A1 and CYP3A using Cyp24a1 knockout rats generated by CRISPR/Cas9 system

Abstract: Edited by F. Peter Guengerich CYP24A1-deficient (Cyp24a1 KO) rats were generated using the CRISPER/Cas9 system to investigate CYP24A1-dependent or -independent metabolism of 25(OH)D3, the prohormone of calcitriol. Plasma 25(OH)D3 concentrations in Cyp24a1 KO rats were approximately twofold higher than in wild-type rats. Wild-type rats showed five metabolites of 25(OH)D3 in plasma following oral administration of 25(OH)D3, and these metabolites were not detected in Cyp24a1 KO rats. Among these metabolites, 25(O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…In contrast, we demonstrated that (23 S )-23-F-25(OH)D 3 ( 1 ) showed stronger resistance to CYP24A1 metabolism than (23 R )-23-F-25(OH)D 3 ( 2 ), as described in our previous study [ 9 ]. These results can be explained by the direction of hydroxylation at the C23 and C24 positions by CYP24A1 [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, we demonstrated that (23 S )-23-F-25(OH)D 3 ( 1 ) showed stronger resistance to CYP24A1 metabolism than (23 R )-23-F-25(OH)D 3 ( 2 ), as described in our previous study [ 9 ]. These results can be explained by the direction of hydroxylation at the C23 and C24 positions by CYP24A1 [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin D 3 is a lipophilic vitamin, and hydroxylation steps promoted by the cytochrome P450 family are essential for both activation and deactivation pathways. In the deactivation step, human cytochrome P450 24A1 (hCYP24A1) is one of the main enzymes catalyzing hydroxylation at the C23 or C24 positions of the 25-hydroxyvitamin D 3 [25(OH)D 3 ] side-chain, and several subsequent hydroxylation steps lead to vitamin D 3 -23,26-lactone or calcitroic acid ( Scheme 1 ) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…C23 hydroxylation and subsequent three-step oxidation lead to vitamin D 3 -26,23-lactone (3). On the other hand, C24 hydroxylation and subsequent five-step oxidation lead to calcitroic acid (4) (Scheme 1) [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…A number of vitamin D derivatives have been approved by the FDA for clinical use in a variety of disorders. These derivatives include calcipotriol (Dovonex; Leo Pharmaceuticals) and 22-oxacalcitriol (Maxacalcitol; Chugai Pharmaceuticals) for treatment of psoriasis; 19-nor-1α,25(OH) 2 D 2 (Zemplar; Abbot Laboratories; Chicago, IL, USA), 26,26,26,27,27,27hexafluoro-(Falecalcitriol; Sumitomo Pharmaceuticals and Taisho Pharmaceuticals), and doxercalciferol (Hectorol; Bone Care Int. ; Middleton, WI, USA) for secondary hyperparathyroidism; and 1α(OH)D 3 (alfacalcidol; Chugai Pharmaceuticals Co., Ltd.; Tokyo, Japan) and eldecalcitol (Chugai Pharmaceuticals Co., Ltd.; Tokyo, Japan) for osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…We have also generated genetically modified rats using genome editing as follows: Cyp27b1-gene-deficient rats (a type 1 rickets model animal), vitamin D receptor-gene-deficient rats, and rats harboring a mutant vitamin D receptor (R270L) gene (type II rickets model animals) [25]. We have also generated Cyp24a1gene-deficient rats to elucidate enzymes and metabolic pathways responsible for vitamin D derivative metabolism [26]. In this review, we describe the in vitro and in vivo systems we have developed for evaluation of vitamin D derivatives, and discuss the derivatives we have synthesized to date.…”
Section: Introductionmentioning
confidence: 99%